Analisis Sentimen Ulasan Pengguna GoPay di Google Play Store menggunakan Model IndoELECTRA - Fitriati, Lisna Rahma; Guntara, Rangga Gelar; Purwaamijaya, Btari Mariska (Jurnal Algoritma, 2025)
The use of digital wallets in Indonesia continues to increase, making it important to analyze user opinions on services such as GoPay. This study analyzes the sentiment of 9,713 GoPay user reviews from the Google Play Store (September 16–October 2, 2025) using the IndoELECTRA model. The research stages included data collection, pre-processing, tokenization, training, and model evaluation. IndoELECTRA produced 95% accuracy and an F1-score of 0.95, demonstrating its strong performance in processing informal Indonesian text. These results confirm the potential of monolingual models in understanding local linguistic contexts compared to some multilingual models. This research contributes to the development of Indonesian NLP, including sentiment evaluation on neutral ratings, although it is limited to Google Play Store data sources and only covers two main sentiment classes.